(untitled) (Journal of Humanities and Social Sciences Research, 2023)
Electronic banking services appeared as a result of laying the foundations for the application of electronic automation in the banking field, and despite the clear expansion in its adoption and implementation as an inevitable necessity imposed by international and national developments, its application was not ideal according to the level that was expected to occur after the abandonment of traditional banking services, which produced some risks Which is evident in the absence of a legal system, whether at the level of proving and authoritative electronic banking services such as electronic signature, Or at the level of protecting the confidentiality of these services and ensuring that they are not exposed to various electronic crimes, especially money laundering crimes, so the challenge has become not in achieving the largest possible profits through the development of banking services, but in how to avoid the risks and losses resulting from that, so we will address in this study the various The motives that imposed the application of electronic automation in the field of banking services, as well as the risks facing the application process, through a statement of the challenges faced by banking institutions when applying the principles of electronic automation in the field of providing banking services in light of the necessity of change and the risks of development.